PENGARUH PERBEDAAN KONSENTRASI BAHAN PADA PENGENCER SPERMA IKAN “ SKIM KUNING TELUR “ TERHADAP LAJU FERTILISASI, LAJU PENETASAN DAN SINTASAN IKAN MAS (CYPRINUS CARPIO L.) - Budi Setyono (Jurnal Gamma, 2009)
Batu, with the aim to determine the effect of different concentrations of materials in fish spermdiluent “Skim Yellow Egg” on the fertilization rate, hatching rate and sintasan carp (Cyprinus carpioL. ). The information gained is expected to assist fish farmers in general and fish hatchery unit orthe people in the context of intensification and efficiency in particular fish spawning carp (Cyprinuscarpio L.)The research method used is an experimental method, a Completely Randomized Design (CRD).Treatment to be studied consisted of 4 treatments and 1 control with 3 replicates, four treatments isthe ratio of diluent materials Skim Yellow Egg.The results of the research are the highest fertilization rate was found in treatment A (53.33%)and lowest in treatment D (37.67%), the rate of hatch (hatching rate) are the highest in treatment A(41.67%) and lowest in treatment D (31.33%), survival (survival rate) are the highest in treatment B(94.67%) and lowest in treatment A (93.33%).The conclusions showed that differences in the concentration of fish sperm diluent “SkimYellow Egg” has a very significant effect on fertilization rate but no effect on hatching rate andsintasana carp (Cyprinus carpio L.). From the results of this study are advised to obtain the bestfertilization rate, should be used in treatment A formulation as follows: 50 ml distilled water, 6.25 gSkim Milk, Egg yolk 3.125 g, 0.625 g Fructose, Penicilin 0.213 g and 0.1 g streptomycin